2010
DOI: 10.1021/jf101477z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dermal Exposure to Nicotiana tabacum (Jean Nicot, 1560) Leaves in Mouse Evaluated by Multiple Methods and Tissues

Abstract: Tobacco farmers are routinely exposed to complex mixtures of the compounds present in tobacco leaves, including organic and inorganic pesticides. Penetration through skin is the most significant route of uptake in occupational exposure to chemicals, including dust and liquids containing toxic and carcinogenic substances. This study evaluates the genotoxic effect of tobacco leaves with and without dermal exposure to flumetralin in Mus musculus, determining cell damage by the micronucleus test and the Comet assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Several studies have described the acute health effects of nicotine toxicity in tobacco workers [45,46]. Genotoxic effects induced by tobacco leaves were investigated only in Mus musculus, where positive results were found [47]. In another study from our group, using the same farm workers from RS an increase in cotinine level during leaf harvest was observed, which confirms exposure to nicotine for this group [48].…”
Section: Tablesupporting
confidence: 69%
“…Several studies have described the acute health effects of nicotine toxicity in tobacco workers [45,46]. Genotoxic effects induced by tobacco leaves were investigated only in Mus musculus, where positive results were found [47]. In another study from our group, using the same farm workers from RS an increase in cotinine level during leaf harvest was observed, which confirms exposure to nicotine for this group [48].…”
Section: Tablesupporting
confidence: 69%
“…Nicotine caused a concentration-dependent increase in DNA fragmentation, as assessed by the Comet assay, in mini-organ cultures of human nasal epithelium, indicating a direct genotoxic effect (Sassen et al , 2005); similar findings have been reported for lymphatic tissue of palatine tonsils and peripheral lymphocytes (Kleinsasser et al , 2005). Nicotine has also been implicated in free radical generation in various types of rodent and human cells, with a direct relationship between reactive oxygen species (ROS) induction and DNA damage (Yildiz et al , 1999; Argentin and Cichetti, 2004; Da Silva et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
“…It is an alkaloid found mainly in plants and is present in high concentrations in tobacco ( Nicotiana tabacum ). Besides being a natural insecticide [5], nicotine is pharmacologically active and has a negative impact on the reproductive system and fertility of males [6, 7]. …”
Section: Introductionmentioning
confidence: 99%